2018
DOI: 10.1590/1519-6984.166522
|View full text |Cite
|
Sign up to set email alerts
|

Biological screening of extracts from leaf and stem bark of Croton floribundus Spreng. (Euphorbiaceae)

Abstract: This work describes the preliminary evaluation of cytotoxic, antimicrobial, molluscicidal, antioxidant and anticholinesterase activities from leaf (LECF) and stem bark alcoholic extracts (BECF) of the species Croton floribundus Spreng. (Euphorbiaceae), popularly known as capixingui or tapixingui. BECF presented significant toxicity (LC50 = 89.6 μg/ml) in the Artemia salina Leach, 1819 (Crustacea: Branchiopoda) bioassay, whereas LECF did not show activity (LC50 > 1000 μg/ml). From DPPH method, the values of IC5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 28 publications
0
2
0
1
Order By: Relevance
“…Confirmando-se esta maior toxicidade pelo menor valor de CL 50 (p < 0,01) apresentado pelo extrato Ppf durante exposição por 48hs, quando comparado a 24hs (Tabela 1), sendo considerada uma alta toxicidade (CL 50 < 100 µg/mL). O fato da significante toxicidade observada pelo extrato Ppf, deve ser considerada como uma característica interessante para utilizar este extrato vegetal para futuros estudos de citotoxicidade 24 . Assim, sugere-se que as folhas P. pseudocaryophyllum também possuem metabólitos ativos que levam toxicidade a artemia, que parecem ser diferentes daqueles encontrados no caule, ou estão de alguma maneira mais concentrados nas folhas.…”
Section: Resultsunclassified
“…Confirmando-se esta maior toxicidade pelo menor valor de CL 50 (p < 0,01) apresentado pelo extrato Ppf durante exposição por 48hs, quando comparado a 24hs (Tabela 1), sendo considerada uma alta toxicidade (CL 50 < 100 µg/mL). O fato da significante toxicidade observada pelo extrato Ppf, deve ser considerada como uma característica interessante para utilizar este extrato vegetal para futuros estudos de citotoxicidade 24 . Assim, sugere-se que as folhas P. pseudocaryophyllum também possuem metabólitos ativos que levam toxicidade a artemia, que parecem ser diferentes daqueles encontrados no caule, ou estão de alguma maneira mais concentrados nas folhas.…”
Section: Resultsunclassified
“…In a complementary manner, by associating the chemical profile of eight plants with the corresponding LC 50 obtained against Brine shirmp, that can be correlated with other biological activities (Barth et al, 2018), it was observed that among species with higher diversity and predominance of flavonoids and phenolic compounds, with higher LC 50 values are the extract of A. humile, G. americana, B. dracunculifolia, C. adamantium McLaughlin et al (1993), which has low toxicity (LC 50 greater than 500 µg mL -1 ); moderate (between 100 and 500 µg mL -1 ) and very toxic (below 100 µg mL -1 ).…”
Section: Discussionmentioning
confidence: 99%
“…The scavenging activity of Pereskia extracts (PAF, PAL, PGF, PGL) on DPPH radicals was determined according to a modified Blois method. 21 Aliquots (0.1 ml) of each extract at a range concentration (62.5, 125, 250, 500, 1000, 2000 μg/ml) were mixed with a DPPH (Sigma-Aldrich®) solution in methanol (2.9 ml at 60 μM) and kept in the dark for 30 minutes. After the incubation period, the absorbance values were measured with a spectrophotometer (Femto, 700 plus model; Brazil) at 517 nm.…”
Section: Evaluation Of In Vitro Antioxidant Activity 22-diphenyl-1-pi...mentioning
confidence: 99%
“…The anticholinesterase activity of the Pereskia extracts (PAF, PAL, PGF, PGL) was assessed by means of a bioautographic assay 25 as previously described. 21 The acetylcholinesterase enzyme (AChE; Sigma-Aldrich®) was dissolved in a tris-hydrochloric acid buffer (0.05 M, pH 7.8) with bovine serum albumin (1 mg/ml, 98%, Sigma-Aldrich®) and stored at 4°C. Aliquots of different volumes (equivalent to 600, 400, 200, 150, 100, 50 and 25 μg dry mass) of each extract stock solution were loaded on TLC F 254 plates (10 x 10 cm, 0.2 mm thickness; Merck®).…”
Section: Evaluation Of In Vitro Anticholinesterase Activitymentioning
confidence: 99%